Exploration of burnout risk factors among mental health nurses - Kleanthous, Efrosyni; Karanikola, Maria (My University, 2011)
Background: A growing body of evidence indicates an increasing incidence of professional burnout among mental health nurses. Aim: Investigation of levels of burnout among mental health nurses and of its associated factors. Method: A critical review of the literature published from 2000 to 2010 was performed, using IATROTEK, PubMed, Cochrane and Cinahl, with the key words: burnout, professional burnout, emotional well-being, work strain, stressors, mental health nurse, psychiatric nurse, with several combinations and links. Only qualitative and quantitative research studies published in English were included, and those in which the sample included mental health professionals other than nurses were excluded. Results: Fourteen relevant studies were found. A significant percentage of mental health nurses report intense professional burnout symptoms. Factors that contribute to burnout symptoms are related to the individual characteristics of the nurses, working parameters and to the characteristics of the patients. Conclusions: Professional burnout among psychiatric nurses is a multidimensional phenomenon. Work factors appear to have a greater impact than the individual characteristics of the nurses.
Keywords: Mental health nurse; Professional burnout; Psychological distress; Risk factors; Stressors; Work strain